We know that by definition i = ( -1 ) Similarly, i*i = ( -1 ) * ( -1 ) = ( -1 )^{2} = -1 By algebra we get: i*i = -1 -i*i = 1 (multiply both sides by -1) -i = 1/i (divide both sides by i)

We know that by definition i = ( -1 ) Similarly, i*i = ( -1 ) * ( -1 ) = ( -1 )^{2} = -1

By algebra we get:

i*i = -1 -i*i = 1 (multiply both sides by -1) -i = 1/i (divide both sides by i)

Contact us | Advertising & Sponsorship | Partnership | Link to us © 2000-2023 Math.com. All rights reserved. Legal Notices. Please read our Privacy Policy.